Exploring pharmacokinetic variability of palbociclib in HR+/HER2- metastatic breast cancer: a focus on age, renal function, and drug–gene interactions - Peruzzi, Elena; Posocco, Bianca; Gerratana, Lorenzo; Nuti, Margherita; Orleni, Marco; Gagno, Sara; De Mattia, Elena; Puglisi, Fabio; Cecchin, Erika; Toffoli, Giuseppe; Roncato, Rossana (Frontiers in Pharmacology, 2024)
Palbociclib, an oral inhibitor of cyclin-dependent kinase 4 and 6, is approved for the treatment of metastatic breast cancer. This study investigated the influence of diverse clinical and biological factors-age, renal function, genetic variations, and comedicationsconcomitant medication (pharmacokinetic covariates)-on palbociclib pharmacokinetics. Employing a validated LC-MS/MS method, we analyzed the minimum plasma concentrations (Ctrough) of palbociclib in 68 women and determined the percentage deviations from the median Ctrough for each dosage group. Variations in a panel of ADME genes were assessed using end-point allele-specific fluorescence detection and pyrosequencing. Two distinct patient cohorts were defined based on median values of age, creatinine, and eGFR, which exhibited statistically significant differences in percentage deviations (p=0.0095; p=0.0288; p=0.0005, respectively). Homozygous carriers of the PPARA variant displayed larger positive percentage deviations compared to the other group (p=0.0292). Similarly, patients concurrently taking CYP3A and P-glycoprotein inhibitors alongside anticancer therapy exhibited significant variations (p=0.0285 and p=0.0334, respectively). Furthermore, exploring the drug-drug-gene interactions between inhibitors of CYP3A and P-glycoprotein with their respective genetic variants revealed two patient groups with statistically different percentage deviations (p=0.0075, p=0.0012, and p=0.0191, respectively). All these results shed light on the pharmacokinetic variability of palbociclib.